Efektivitas Promosi Kesehatan oleh Teman Sebaya melalui Modul Edukasi Online terhadap Pengetahuan Remaja Putri tentang Perkawinan Usia Anak untuk Pencegahan Stunting - Lily Yuniar; Erni Juniartati; Marsia Marsia (Jurnal Ners, 2026)
Child marriage is a risk factor contributing to increased stunting prevalence, particularly among adolescent girls with limited knowledge of reproductive health. Adolescents are highly influenced by their environment; therefore, an effective health promotion strategy is crucial. Peer-based education using online learning modules offers interactive features and easier accessibility, making it a promising method to improve adolescent understanding. This study aimed to determine the effectiveness of peer-assisted online educational modules in increasing adolescent girls’ knowledge about child marriage as part of stunting prevention efforts. A quasi-experimental design with a pretest–posttest control group was applied involving 44 adolescent girls selected through probability sampling. The intervention group received an online educational module, while the control group was given a printed module. Study results showed a significant increase in knowledge among the intervention group after receiving the online module, with a p-value of 0.000 (<0.05) based on the Wilcoxon test. These findings indicate that peer-based online educational modules effectively improve adolescents’ understanding of the risks associated with child marriage and the importance of stunting prevention.